Radical nephrectomy combined with removal of tumor thrombus from inferior vena cava under real-time monitoring with transesophageal echocardiography: A case report. Issue 11 (March 2020) - Wang, Yaozhu; Wang, Xu; Chang, Yuan
Abstract: Rationale: Renal carcinoma is a common malignant tumor of the urinary system, 4%–10% of which are complicated with tumor thrombi in the renal vein and the inferior vena cava; in about 1% of patients, the inferior vena cava tumor thrombus invades the right atrium. Surgery is the treatment of choice. Real-time monitoring with transesophageal echocardiography (TEE) has been widely used in various operations, including cardiac and non-cardiac operations for congenital heart diseases, coronary diseases, vascular heart diseases, and aorta diseases, etc. In this article, a case of a patient with right renal carcinoma complicated with an inferior vena cava tumor thrombus is reported. Patient concerns: A 52-year-old man who was admitted to our hospital for lumbar pain lasting for one month. Diagnosis: Right renal carcinoma complicated with an inferior vena cava tumor thrombus. Interventions: Radical nephrectomy of the renal carcinoma and removal of an inferior vena cava tumor thrombus under real-time monitoring with TEE were performed. Outcomes: Radical nephrectomy was successfully performed within 5 minutes after the inferior vena cava was clamped, and then the inferior vena cava tumor thrombus was removed. On the second day after the operation, the patient's conditions improved; his consciousness was clear; he was transferred to a general ward. On the third day after the operation, the patient was able to get out of bed and was discharged on the sixth day after the operation. Lessons: Real-time monitoring with TEE played an important role in many aspects in the radical nephrectomy of the renal carcinoma and removal of the inferior vena cava tumor thrombus.